2022-RA-1086-ESGO Sebaceous carcinoma (SC) of the vulva – a case report and literature review. (20th October 2022) - Zeinah, Hassan; Owens, Gemma; Jones, Sadie; Lim, Kenneth; Howells, Robert; Boyde, Adam; Rzyska, Ewelina; Sharma, Aarti
Abstract : Introduction/Background: Sebaceous carcinoma (SC) is a rare cutaneous malignancy arising from sebaceous glands most commonly in the periocular region. Very rarely, it occurs in the vulva. There are 12 cases published in the literature of extraocular sebaceous carcinoma of the vulva. We present a case of 59-year-old woman with persistent vulval symptoms and confirmed histological diagnosis of SC. Methodology: Review of the patient's case notes, external expert histopathology opinion and published literature. Results: The patient first presented at 51 years with vulval itching and soreness. She underwent wide local excision (WLE) of the lesion which confirmed high grade vulval intraepithelial neoplasia (VIN 3). Over the years, she had several biopsies for persistent vulval symptoms. Interestingly, patient's symptoms were exacerbated with use of topical/systemic steroids. All biopsies showed similar histology of VIN 3. At 57 years, further WLE showed a stage 1A squamous cell carcinoma of the vulva (completely excised). At 59 years, vulval biopsies were taken for ongoing symptoms. An external histopathological review confirmed extra-ocular SC. She underwent anterior vulvectomy for the diffuse lesion and is now planned to undergo a bilateral groin lymph node dissection as histology showed poor differentiation and lymphovascular space invasion. Conclusion: This is the 13th case reported of SC of vulva. In women with persistent vulval symptoms, it's crucial to consider in differential diagnosis and to seek expert histopathological opinion when suspected.